Actinobacteria Derived from Algerian Ecosystems as a Prominent Source of Antimicrobial Molecules - Ibtissem Djinni; Andrea Defant; Mouloud Kecha; Ines Mancini (MDPI AG, 2019)
Actinobacteria, in particular “rare actinobacteria” isolated from extreme ecosystems, remain the most inexhaustible source of novel antimicrobials, offering a chance to discover new bioactive metabolites. This is the first overview on actinobacteria isolated in Algeria since 2002 to date with the aim to present their potential in producing bioactive secondary metabolites. Twenty-nine new species and one novel genus have been isolated, mainly from the Saharan soil and palm groves, where 37.93% of the most abundant genera belong to Saccharothrix and Actinopolyspora. Several of these strains were found to produce antibiotics and antifungal metabolites, including 17 new molecules among the 50 structures reported, and some of these antibacterial metabolites have shown interesting antitumor activities. A series of approaches used to enhance the production of bioactive compounds is also presented as the manipulation of culture media by both classical methods and modeling designs through statistical strategies and the associations with diverse organisms and strains. Focusing on the Algerian natural sources of antimicrobial metabolites, this work is a representative example of the potential of a closely combined study on biology and chemistry of natural products.